PELAKSANAAN PENDIDIKAN PADA MADRASAH DINIYAH DI PROPINSI NUSA TENGGARA BARAT - Wahab Wahab (Analisa: Journal of Social Science and Religion, 2008)
This research aims to describe educational implementationat Madrasah Diniyah, West Nusa Tenggara Province. The researchperformed in ten Madrasah Diniyah. The results show thateducational implementation at Madrasah Diniyah is relative simple.This could be observed in curriculum implementation that are alltheir own products and only small amount have added lessons usedfor UAN (National Final Exam, for elementary school and juniorhigh school). That self-made curriculum is very simple; only contain kindof course and their teachers. Education methods used by the teachersI ustadz are translation, less explanations I lecture, and qiroah. Inimplementing education, not all teachers prepare pre-test and posttest. Educational evaluations performed at Madrasah Diniyah tendto cognition ability of the students, that is their reading holy bookskills and religious know ledges. Only few Madrasah Diniyahimplemented skill education for their students. In performingeducational implementation at Madrasah Diniyah, the teachers donot prepare learning programs in first place; such as weeklyprograms, semester programs, and annual programs. Moreover, ifwe take a look on educational infrastructures using in this learningare relative simple, only sit on the floor, not all in the class room,minimal display, etc. From competency point of view, the teachers at Madrasah Diniyah are less relevant in their alumni. Only few of the teachers atMadrasah Diniyah graduate from educational institutions, majority are Islamic boarding house alumni.